A critical analysis of the human trafficking legal framework in Hong Kong: efficacy and recommendations - Noble Po Kan Lo (Cogent Social Sciences)
This study critically examines the framework governing human trafficking within the Hong Kong Special Administrative Region (HKSAR), emphasizing its effectiveness in deterring and addressing this serious issue. Despite a growing number of trafficking incidents highlighted by the local press, this analysis contends that the HKSAR’s legal provisions are not entirely consistent with global norms, particularly the Palermo Protocol and the UN Convention against Transnational Organized Crime. By juxtaposing the HKSAR’s legal strategies with the United Kingdom’s Modern Slavery Act, 2015 and Australia’s laws criminalizing human trafficking and slavery, which are contained within Divisions 270 and 271 of the Commonwealth Criminal Code Act 1995 (Criminal Code), notable legal shortcomings are identified, especially the inadequate coverage of non-sexual exploitation and the lack of corporate accountability in supply chains. The paper posits that while the existing legal structures in Hong Kong have certain strengths, their deficiencies, coupled with societal and criminal challenges such as organized crime and corruption, exacerbate the region’s trafficking problems. The analysis suggests that adopting reforms similar to those in the UK, including the potential introduction of a ‘failure to prevent’ trafficking offense for corporations, could significantly enhance the HKSAR’s efforts against human trafficking.